Jaringan Perdagangan Garam di Sumenep Abad ke-19 - Syifaul Qalbiyah; Ari Sapto; Daya Negri Wijaya (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Since the nineteenth century, Sumenep has served as an important center of salt production and trade in Madura within the maritime economy of the Dutch East Indies. Its strategic geographical location, the availability of port facilities, and the maritime activities of local communities enabled Sumenep to be integrated into inter-island trade networks across the region. Nevertheless, studies on Sumenep’s role in the salt trade routes have tended to focus primarily on economic aspects and colonial policies, leaving the strategic significance of this area insufficiently explored from a maritime historical perspective. This research aims to reconstruct the salt trade network of Sumenep in the nineteenth century by emphasizing the role of ports, trade actors, and the relationship between colonial regulations and the economic activities of coastal communities. The study employs a historical method consisting of topic selection, heuristics, source verification, interpretation, and historiography. Research data are derived from Dutch-language colonial newspaper archives, colonial government reports, and relevant historical literature. The findings reveal that the Port of Sumenep functioned as a collecting center linking salt-producing areas with regional trade networks within the framework of the colonial monopoly system. Trade activities involved salt producers, intermediary traders, traditional maritime shipping, and colonial authorities, while informal trade routes emerged as strategies of economic adaptation and resistance among coastal communities. The study concludes that salt trade activities in Sumenep were not merely a representation of colonial power but also reflected dynamic processes of negotiation and local economic resilience in response to the colonial monopoly system.